Identify of Seawater Intrusion Using Hydrochemical Approach and Fuzzy Logic for the Ain Zara, Libya. (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
Coastal freshwater aquifer contamination by saline seawater is a significant threat to groundwater quality. This contamination is known as Seawater Intrusion (SWI). It leads to an increase in groundwater salinity, presenting both environmental and health risks. This study aims to assess seawater intrusion into the groundwater of the Ain Zara region, located south of Tripoli, by evaluating the relationship between Electrical Conductivity (EC) and Chloride (Cl-) concentrations in the groundwater, as well as Simpson’s Ratio (SR), the Groundwater Quality Index for Seawater Intrusion (GQISWI), the Seawater Mixing Index (SMI), and Hydrochemical Evolution Facies (HEF) diagrams. Additionally, a Fuzzy Seawater Intrusion Index (FSWI) model was developed, which uses fuzzy logic to assess the degree of seawater contamination in the aquifers. Forty groundwater samples were collected from wells in the study area in March 2023. The physico-chemical properties of the groundwater samples were Electrical Conductivity (EC), Total Dissolved Solids (TDS), pH, and major dissolved ions such as Sodium (Na+), Potassium (K+), Calcium (Ca2+), Magnesium (Mg2+), Chloride (Cl-), Bicarbonate (HCO3-), and Sulfate (SO42-). Additionally, the Potential Salinity (PS) was calculated. Four parameters were included in the FSWI model i.e.,TDS (mg/L), Cl- (mg/L), EC (µS/cm), and PS (mg/L).The results showed high variation coefficients for Chloride, Sodium, Calcium, and Total Dissolved Solids compared to the other ions, indicating the distinct chemical composition of the region's well waters. Additionally, the low variation coefficients for Bicarbonate and pH reflect the relative stability of these properties in the groundwater. The values of the seawater intrusion indicators revealed that the area is at risk of seawater intrusion, and it is following the same spatial distribution pattern. The developed FSWI model can reliably estimate the degree of seawater contamination in the groundwater. The obtained results highlight the urgent need for measures to mitigate this issue.
Keywords: Hydrochemical Characteristics; Seawater Intrusion Indicators; Fuzzy Logic; Ain Zara; Libya